Evaluation of novel anti-cancer drugs using a D.melanogaster cancer model coupled to AP-MALDI mass spectrometry imaging - Wong, Kei Fung Carver / KFC (2025)
Cancer therapeutics is a continuous challenge to develop treatment options that are sufficient in bypassing clinical issues of cancer resistance and recurrence. Combination chemotherapy strategies have been successful due to synergistic interactions arising from multiple agents. As such, novel insights in modern pharmacology aim to develop multi-target drug compounds capable of influencing multiple biological processes using a singular agent. Currently, most multi-target agents have utilised a histone deacetylase (HDAC) inhibiting pharmacophore as a scaffold. Here, a novel tubulin and HDAC inhibiting dual-target agent, TH-6, was evaluated alongside its single-target tubulin-inhibiting backbone, TH-9, using an in vivo Drosophila melanogaster pupal cancer model coupled to analytical atmospheric-pressure matrix-assisted laser desorption/ionisation (AP-MALDI) mass spectrometry (MS) imaging. An established in vivo Drosophila pupal model system was used to generate a hyperproliferative tumour phenotype in the pupal notum. The hyperproliferation is driven by aberrant mTOR signalling induced through the knockdown of TSC1. To facilitate drug investigation using this Drosophila model, a 6-/12-well plate system of drug screening was developed to improve the model’s robustness for drug research. Quantitative confocal microscopy analysis of proliferation-related clonal phenotypes demonstrated the model’s capability for pharmacological studies when analysing the impact of rapamycin, a direct inhibitor of the model, against tamoxifen, an agent without a functional target in flies. The drug-dose dependency of rapamycin was achieved in the model serving as a foundation for dosage selection when testing other agents. To prepare Drosophila cancer model pupae for MS analysis, a procedure to freeze, embed and cryosection of the samples was developed. AP-MALDI MS imaging (MSI) was performed on rapamycin-treated cancer pupae demonstrated that the drug-induced metabolomic and lipidomic alterations could be detected. Following this, novel agents, TH-6 and TH-9, and commercial single-target counterparts, combretastatin A-4 (CA-4) and vorinostat (SAHA), were analysed using the established workflow. The conventional microscopy approach demonstrated that TH-6 and TH-9 performed comparably with rapamycin and better than the commercial agents. AP-MALDI MSI detected stark differences in the metabolomic and lipidomic response profile of drug-treated pupae against those untreated. Several metabolites, namely arginine, lysine, and carnitine metabolites, were found to be strongly associated with the drug activity of TH-6 and TH-9. Suppression of hyperproliferation in the model was also found to be related to the reduction of glycerophospholipids for all drug agents. This study demonstrates the potential for the novel dual-target agent TH-6 as an anticancer agent for highly proliferative cancer subtypes. These findings also highlight the established platform’s ability to integrate traditional and advanced workflows, offering a versatile tool for drug discovery and mechanistic studies.